Hamlet : Prince of Denmark - Shakespeare, William; Deighton, K. (Kilkenny, S.A. : Moore Books SA, 2014)
A play presenting the story of Hamlet, told to the audience by a small group of actors, using snippets of Shakespeare's language.
Hamlet, Prince of Denmark by Martha Lott was first produced by Holden Street Theatres and The Recycled Theatre Company duing the Adelaide Fringe, February to March 2013, at Holden Street Theatres, Hindmarsh, Adelaide. It was again presented during the Adelaide Fringe, February to March 2014, at Holden Street Theatres.
Keywords: English drama; Australian